2017
DOI: 10.4028/www.scientific.net/amm.863.368
|View full text |Cite
|
Sign up to set email alerts
|

Development of CAD Model Annotation System Based on Design Intent

Abstract: Most of the product design on the market is variant design or adaptive design, which need to reuse existing product design knowledge. A key aspect of reusing existing CAD model is correctly define and understand the design intents behind of existing CAD model, and this paper introduces a CAD model annotation system based on design intent. Design intents contained all design information of entire life cycle from modeling, analysis to manufacturing are marked onto the CAD model using PMI module in UG to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Other mechanisms based on word mappings, multiple-domain matrices, and especially annotations are considered more natural and intuitive, and thus more useful for providing a general view of the information and the relationships between items of information (Rasoulifar, Eckert, & Prudhomme, 2014). In this context, advances in the areas of model-based definition (MBD) and product manufacturing information (PMI) have enabled the development of new markup tools and annotation-based mechanisms for CAD where information is linked directly to part geometry (Sandberg & Na¨sstro¨m, 2007;Lundi, Lejon, Dagman, N ässtr öm, & Jeppsson, 2017;Ma, Song, Xie, & Zhou, 2017). Authors Jones et al (2020) recently experimented with a model-based approach to information access to improve engineering information retrieval, which even allows for nontext documents to be indexed.…”
Section: Related Workmentioning
confidence: 99%
“…Other mechanisms based on word mappings, multiple-domain matrices, and especially annotations are considered more natural and intuitive, and thus more useful for providing a general view of the information and the relationships between items of information (Rasoulifar, Eckert, & Prudhomme, 2014). In this context, advances in the areas of model-based definition (MBD) and product manufacturing information (PMI) have enabled the development of new markup tools and annotation-based mechanisms for CAD where information is linked directly to part geometry (Sandberg & Na¨sstro¨m, 2007;Lundi, Lejon, Dagman, N ässtr öm, & Jeppsson, 2017;Ma, Song, Xie, & Zhou, 2017). Authors Jones et al (2020) recently experimented with a model-based approach to information access to improve engineering information retrieval, which even allows for nontext documents to be indexed.…”
Section: Related Workmentioning
confidence: 99%
“…The use of annotations as carriers of design and engineering knowledge has been empowered with new developments in Model-Based Definition (MBD) standards and Product Manufacturing Information (PMI) tools. For example, several authors have suggested the use of 3D annotations to enrich CAD models with design information [16][17][18][19]. This approach takes advantage of the global availability of product information across the enterprise as well as the functionality of PDM systems to share this information between the different stakeholders that participate in the development process.…”
Section: Related Workmentioning
confidence: 99%